PROCEDURE FOR GENERATING SYNTHETIC DATA FOR THE DEVELOPMENT OF ALGORITHMS TO SOLVE THE INVERSE PROBLEM OF SEISMIC EXPLORATION - Valiyev K.A.; Repin V.N. (My University, 1989)
In this report the authors suggest a technique for deriving synthetic data which is not only useful for evaluating and comparing the efficiency of the existing algorithms, but can also lead to new algorithms for the reconstruction of the interior structure of the earth. The technique is based on the assumption that microelectronics technology is capable of producing a structure whose acoustic properties would be the same as those of the real geologic formation. In other words, the authors discuss how to simulate the interior structure of the earth by means of microelectronic devices, that is, how to create a structure on a silicon substrate that would be acoustically similar to the sedimentary layers of the earth. A comparison of the sections of geologic structures and integrated circuits reveals striking similarities. Just as the sedimentary series of the earth, in the integrated circuit we also find a complicated, layered structure made up of different materials. The electric, mechanical and other properties of these materials differ strongly. We shall be interested in their acoustic properties, first of all, in the speed of travel of acoustic waves in them. The velocities determined by seismic exploration generally lie in the range of 3000 to 6000 m/s. The materials used in electronics exhibit about the same range of speeds of sound. Another, not less important acoustic property is the coefficient of sound absorption. To simulate it in an integrated circuit, the following similarity condition must be fulfilled. Here the acoustic properties, especially the velocity, are considered for development of the algorithms able to solve inverse problems of seismic exploration.